Physical, structural and mechanical properties of foam glass-ceramics derived from waste soda-lime-silica glass and clamshell - Noor Hisham, Noor Aizat (2021)
Nowadays, municipal solid waste has risen to a very alarming level throughout the nation. Our country is heavily dependent on open dumping and landfills, although these methods are expensive and time-consuming. The enormous number of solid waste management problems has encouraged scientists and researchers to think about converting waste materials into other beneficial materials. Therefore, an initiative has been taken through this research to utilize the soda-lime-silica (SLS) waste as the glass matrix and the source of silicon (SiO2) and clamshell (CS) as the foaming agent (pore former) to fabricate the light-weight foam glass-ceramics (FGC). A series of FGC samples with 1, 3, 6 and 9 wt.% CS were successfully prepared by the conventional solid-state sintering method at 700, 800 and 900 C sintered for 30, 60 and 120 min. The physical, structural, and mechanical properties of the raw materials and FGC were characterized by wavelength dispersive X-ray fluorescence (WDXRF), thermogravimetric analysis (TGA) density, linear expansion, total porosity, X-ray diffraction (XRD), fourier transform infrared (FTIR), field-emission scanning electron spectroscopy (FESEM) and compressive strength measurement. From the result of WDXRF to study the chemical composition of raw materials, SLS glass mainly composed of 71.90 wt.% of SiO2 meanwhile CS has high weight percentage of CaO which is 53.41 wt.%. Based on these results, CS is found to contain 98.60 wt.% CaCO3. For the structural properties of raw materials, the XRD pattern of SLS glass reveals no continuous or discrete sharp peak with a broad feature of the amorphous halo at an angle around 2θ = 20 to 40° and meanwhile, the shape of the CS powder peak signifies the reflection of the aragonite crystalline phase with an orthorhombic crystal system. Based on TGA profile of CS, the thermal properties of CS indicate the gradual decline of CaCO3 had occurred after undergoing the thermal treatment around 860 C with a weight loss of approximately 43.56 %. The bulk density of the FGC samples is found to achieve minimum density (0.525 g/cm3) with maximum expansion (83.98 %) at 3 wt.% CS sintered at an optimum sintering temperature and holding time which is 800 C for 60 min. The bulk density increases as the linear expansion and total porosity decreases with the progression of CS contents, sintering temperature, and holding time, where the results agree with the FESEM micrograph. The result of XRD and FTIR transmittance spectra have shown the formation of wollastonite crystal starting at 3 wt.% CS sintered at 800 C for 30 min. The crystallization of the wollastonite crystal phase increases with the progression of CS content, sintering temperature, and holding time. The trend of the compressive strength corresponds well with the trend of the bulk density. The highest mechanical performance (0.78 MPa) with an acceptable low bulk density (0.612 g/cm3) and average total porosity (74.81 %) is obtained for the sample containing 3 wt.% CS sintered at an optimum temperature and holding time. It can be concluded that the compressive strength increases with the decrease in linear expansion and the total porosity value of the FGC. The overall result promotes that the FGC derived from SLS glass and CS waste materials have a high potential to be used as concrete aggregate materials in the building and construction industry.